A argumentação no gênero discursivo contrato: uma análise dos modalizadores discursivos - Deus, Kátia Régina Gonçalves de (2016)
The main purpose of this research is to analyze and describe the semantic-argumentative operation of modalizers in genre Contract, whose purpose is to establish an agreement between persons transferring, to one another, certain rights or are subject to obligations. The theory that our work embrace is based on studies of Modalization Discourse, presented by Lyons (1977), Cervoni (1989), Koch (2009), Castilho and Castilho (2002), Neves (2010), Nascimento and Silva (2012) among others, as well as the theory of genres proposed by Bakhtin (2000 [1979]). In addition to this contribution, this work is also based on Argumentation theory of Language proposed by Ducrot and collaborators (1988). Our corpus is composed by ten (10) contracts that were collected in public and private institutions, as well as world wide web. These contracts were divided as follows: in ten contracts selected, five are contracts for service and the other half are lease agreements. This research has a qualitative, descriptive and an interpretive nature, as we describe the semantic-argumentative operation of modalizers and meaning effects caused by its use in the objects of research texts. The theory the we have adopted allowed us to understand how these modalizers work strategically in this genre. We observed, over the analysis, that the deontic modals of obligation, the delimiters and volitional deontic, not only because of the number of occurrences, but mainly due to the role they play in the text itself, constitutes an integral part of the very structure of the contracts and, therefore, are characteristic of the linguistic style of this genre. Given these findings, it was concluded, about the genre contract, that the argumentativity (subjectivity and intersubjectivity) is present in this type of text, among other strategies, the presence of deontic modals of obligation, delimiters and volitional deontic. This reveals in the writing process of the genre, the subjective marks of the speakers will be recorded through the use of modalizers, that allowed to reveal the direction they want to give to the meaning of the statements, Furthermore, the modals highlight the assumed front positions to content said.